2007
DOI: 10.1002/jhet.5570440633
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of benzo[b][1,4]thiazepines by the reaction of 3‐aryl‐1‐(3‐coumarinyl)propen‐1‐ones with 2‐aminothiophenol

Abstract: 3‐(2‐Aryl‐2,3‐dihydro‐benzo[b][1,4]thiazepin‐4‐yl)chromen‐2‐ones (2a, e, f) and (Z)‐3‐(2,3‐dihydro‐2‐arylbenzo[b][1,4]thiazepin‐4(5H)‐ylidene)chroman‐2‐ones (3a‐f) have been synthesized by the reaction of 3‐aryl‐1‐(3‐coumarinyl)propen‐1‐ones (1a‐f) with 2‐aminothiophenol in a hot mixture of toluene and acetic acid. Structures of all new compounds and their complete 1H and 13C assignments were achieved applying different one‐ and two‐dimensional nmr experiments in combination with various spectroscopic techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…16 A search for the applied methods for synthesis of medium-sized N,S-heterocyclic systems demonstrated that several established protocols are in practice, and comprehensive reviews of the syntheses and biological activities of various benzo-condensed 1,3-, 1,4-, 1,5-thiazepine and thiazocine regioisomers have been published. [17][18][19][20][21][22][23] Formation of thiazonines and higher ring systems, however, remains unknown. Most of the reported strategies for the synthesis of 1,4-thiazocine and higher ring frameworks are presented in a few select publications.…”
Section: Introductionmentioning
confidence: 99%
“…16 A search for the applied methods for synthesis of medium-sized N,S-heterocyclic systems demonstrated that several established protocols are in practice, and comprehensive reviews of the syntheses and biological activities of various benzo-condensed 1,3-, 1,4-, 1,5-thiazepine and thiazocine regioisomers have been published. [17][18][19][20][21][22][23] Formation of thiazonines and higher ring systems, however, remains unknown. Most of the reported strategies for the synthesis of 1,4-thiazocine and higher ring frameworks are presented in a few select publications.…”
Section: Introductionmentioning
confidence: 99%